2019
DOI: 10.1111/tgis.12535
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal land use multi‐objective optimization: A case study in Central China

Abstract: Much effort has been applied to the study of land use multi‐objective optimization. However, most of these studies have focused on the final land use scenarios in the projected year, without considering how to reach the final optimized land use scenario. To fill this gap, a spatio‐temporal land use multi‐objective optimization (STLU‐MOO) model is innovatively proposed in this research to determine possible spatial land use solutions over time. The STLU‐MOO is an extension of a genetic land use multi‐objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Land use optimization has been broadly studied in the past decades towards various concerns or objectives [5][6][7][8][9][10][11][12][13][14]. However, there has not been many studies specifically on the livability oriented land use optimization except some general discussions and interpretation on livability from various perspectives of researchers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Land use optimization has been broadly studied in the past decades towards various concerns or objectives [5][6][7][8][9][10][11][12][13][14]. However, there has not been many studies specifically on the livability oriented land use optimization except some general discussions and interpretation on livability from various perspectives of researchers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another kind of effective method is the abovementioned "weighted-sum" method. Although it cannot yield non-convex optimal solutions, it has still been commonly used because of its simplicity and effectiveness for most of the multi-objective optimization problems [6,9,36,37]. In this research, the goal programming and weighted-sum methods are used to construct the land use optimization model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Each of these formats has its own advantages and disadvantages. Using the raster format facilitates the definition of the neighborhood, chromosomes encoding, and the application of GA operators because the computations can be conducted on a regular grid (Cao, Zhang, & Wang, 2019; Handayanto, Tripathi, Kim, & Guha, 2017; Mohammadi et al., 2016; Schwaab et al., 2018; Shaygan et al., 2014; Song & Chen, 2018; Stewart et al., 2004). However, the raster format is dependent on the size of grid cells (resolution).…”
Section: Spatial Urban Land Use Allocation Modelmentioning
confidence: 99%
“…In specialized and complex problems such as ULUP, in which the objective functions, input data, and problem details have a particular format and do not have a standard form, it is necessary to make significant changes to adapt the algorithms to the problem. Previous researchers (Cao, Zhang, & Wang, 2019; Cao et al, 2011; Masoumi et al, 2017; Masoumi et al, 2020; Schwaab et al, 2018) have shown that in some cases the use of these algorithms in the ULUP problem does not create a diverse and well‐ordered solution space. Therefore, the goal here is to balance the density of the solutions in the PF and to achieve a wider variety of solutions based on the use of the NSGA‐III.…”
Section: Introductionmentioning
confidence: 99%
“…Among various ecological factors, Ecosystem Services Value (ESV), namely the value of ecosystem service and natural capital estimated by economic rules, is widely used due to its clear scientific significance and ease of calculation [24][25][26]. In addition, Net Primary Productivity (NPP), soil erosion, and pollution control can be chosen if necessary to accord with environmental protection policies [27,28]. For the social benefit measurement, compatibility or incompatibility of land use is most often adopted [29][30][31], while compactness and conflict degree (between neighboring land use localities) are also used for social objectives [3,32,33].…”
Section: Introductionmentioning
confidence: 99%